Fostering Employee Engagement through Leadership and Perceived Organizational Support: Mediating Role of Employee Satisfaction in Travel Companies - Nova Eviana; Rudhi Achmadi; Lenny Yusrini; Maeenuddin (African Journal of Hospitality, Tourism and Leisure, 2022)
Employee engagement becomes the most important driving factor for a company's business processes due to its ability to increase the positive employees’ motivation, and both individual and companies’ performances. Some studies explain the positive influence of leadership and POS on employee engagement, though, some research results otherwise. This inconsistency is predicted due to another variable that mediates the influence of leadership and POS on employee engagement. This study aims to analyze the direct and indirect influence of leadership and POS on employee engagement with employee satisfaction as a mediation variable. Data were collected by using a questionnaire instrument distributed to a total of 77 employees of the travel company. Data was analyzed using SEM PLS with the assistance of Smart PLS software. The results showed that only leadership and employee satisfaction have a direct and significant effect on employee engagement. In contrast, POS has no direct effect on employee engagement, due to the inexistence of the supporting process, such as employees' intrinsic and extrinsic motivation. Employee engagement therefore could be an antecedent factor toward employee satisfaction or performance. Both leadership and POS had a positive and significant indirect influence on employee engagement by being mediated by employee satisfaction.